2018
DOI: 10.1101/293886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-saccadic remapping relies on dynamics of spatial attention

Abstract: Each eye movement shifts the projections of the visual scene on the retina. It has been proposed that the receptive fields of neurons in oculomotor areas are remapped pre-saccadically to account for these shifts. While remapping of the whole visual scene seems prohibitively complex, selection by visual attention may limit these processes to a subset of attended locations. Because attentional selection consumes time, remapping of attended locations should evolve in time, too. In our study, we cued a spatial loc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In contrast to awareness being not necessary for the spatiotopic updating, the buildup of spatiotopic neural representation requires spatial attention (Crespi et al, 2011;Melcher, 2008;Melcher, 2009;Melcher, 2011;Melcher & Colby, 2008;Szinte et al, 2018). Crespi et al (2011) found that when participants were conducting a demanding attention task on the foveal stimuli, BOLD responses evoked by moving stimuli unrelated to the fovea task were mainly tuned in retinotopic coordinates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to awareness being not necessary for the spatiotopic updating, the buildup of spatiotopic neural representation requires spatial attention (Crespi et al, 2011;Melcher, 2008;Melcher, 2009;Melcher, 2011;Melcher & Colby, 2008;Szinte et al, 2018). Crespi et al (2011) found that when participants were conducting a demanding attention task on the foveal stimuli, BOLD responses evoked by moving stimuli unrelated to the fovea task were mainly tuned in retinotopic coordinates.…”
Section: Discussionmentioning
confidence: 99%
“…While the input visual information during saccades is suppressed, our conscious representation of the visual scene across saccades seems to be smooth and continuous, yet we typically do not keep track of the whole visual scene. Selective attention is one of the potential mechanisms to help maintain visual stability (Crespi, Biagi, d'Avossa, Burr, Tosetti, & Morrone, 2011;Melcher, 2008;Melcher, 2011;Szinte, Jonikaitis, Rangelov, & Deubel, 2018). Attentional selection contributes to visual stability by restricting information processing to salient or task-relevant objects.…”
Section: Introductionmentioning
confidence: 99%
“…Such a supra-modal topological map could allow multi-sensory space constancy via predictive remapping of locations as a function of their ability to attract spatial attention (Cavanagh, Hunt, Afraz, & Rolfs, 2010;Rolfs & Szinte, 2016;Szinte, Jonikaitis, Rangelov, & Deubel, 2018) rather than as a function of their modality. As an alternative, one could propose that multiple reference frames are simultaneously maintained.…”
Section: Discussionmentioning
confidence: 99%
“…This modulation appears to depend on fast presaccadic shifts of attention (1,3). Even before the eye starts to move, peripheral vision is enhanced (4)(5)(6)(7)(8), and sensory tuning is reshaped at the saccade target location; the gain of high spatial frequencies increases (9,10), and orientation tuning narrows (5,9). These changes occur only briefly, from approximately 60 to 100 ms before the onset of a saccade (4,5,(9)(10)(11)(12)(13), and have a profound influence on visual perception, as humans perform saccades every few hundred milliseconds.…”
mentioning
confidence: 99%
“…This effectively offers a glimpse of what is going to fall at the center of gaze after the saccade (14). In addition, presaccadic attention is also believed to play a role in maintaining spatial stability across saccades (6,9,(15)(16)(17) and in keeping track of the attended objects across saccades (6,13,18).…”
mentioning
confidence: 99%